Single Moving Average (SMA) Analysis for Gold Jewelry Sales a Pegadaian Outlet Labuhan Ruku - Rozi Juliantika; Neni Mulyani; Sudarmin Sudarmin (SAINTIS Publishing, 2025)
This study aims to analyze gold bullion sales at the Pegadaian Labuhan Ruku Outlet using the Single Moving Average (SMA) method as a forecasting tool. Forecasting, which involves estimating future events based on historical data, is essential in business decision-making, particularly in inventory and financial planning. The SMA method was chosen for its simplicity and effectiveness in identifying sales trends over time. Using monthly gold sales data from January 2024 to January 2025, this study predicts future sales to help the company respond to market demand. The results show that gold sales fluctuate due to factors such as global gold price changes and consumer purchasing behavior. The SMA method successfully produced accurate sales forecasts with a low error rate, proving its reliability for short-term prediction. In conclusion, implementing the SMA forecasting method can support Pegadaian in managing stock more efficiently, minimizing excess inventory, and improving responsiveness to market trends. This suggests that even simple forecasting techniques can provide valuable insights and play a strategic role in business operations.